Four new species of Myrsidea Waterston chewing lice (Phthiraptera: Menoponidae) from the Malagasy warblers (Passeriformes) - Price, Roger D.; Johnson, Kevin P. (Zootaxa, 2006)
Four new species of the menoponid genus Myrsidea Waterston are described from the Malagasy warblers. These new species and their type hosts are: M. yoshizawai ex the Short-billed tetraka, Xanthomixis zosterops andapae (Salomonsen); M. goodmani ex the Long-billed bernieria, Bernieria madagascariensis madagascariensis (J.F. Gmelin); M. mccrackeni ex the White-throated oxylabes, Oxylabes madagascariensis (J.F. Gmelin); and M. batesi ex the Long-billed bernieria, B. m. madagascariensis (J.F. Gmelin). These represent the first species of Myrsidea to be described from this group of hosts. We also sequenced a portion of the mitochondrial COI gene for these and other species of Myrsidea.